Estimating potential woody biomass supply under sustainable timber production from plantation forests in a snowy mountainous region of Japan - Tatsuhara, Satoshi (Array, 2020)
Numerous woody biomass-powered stations for energy generation have been constructed in Japan since the Feed-in Tariff Scheme was introduced. However, a stable, long-term woody biomass supply from plantation forests is necessary for the construction and operation of such power stations. The logs that are used to produce fuel chips are harvested from roundwood. Thus, the main objective of this study was to estimate the potential supply of woody biomass resources under the condition of maximum sustainable harvesting from privately-owned plantation forests. Another aim was to examine the stability of sustainable harvest volumes from periodical changes. The study focused on privately-owned forests in the Sampoku district of Murakami City in the northernmost part of Niigata Prefecture, Japan. Trees in the studied region are commonly bent during periods of high snowfall, and the current bucking strategy – influenced by the construction of a biomass-powered generation facility – was integrated into the model. The revenues and costs of plantation management and timber production were calculated based on stands’ geographical attributes using a geographic information system. A mixed integer programming model was used to predict the maximum sustainable harvest levels that would provide stable profits. The simulation showed that even though the trees had a unimodal age class distribution, sustainable harvest volumes ensured a sustainable supply of woody biomass over various rotation ages. Extending the range of rotation ages by 20 years dramatically increased the potential supply of woody biomass resources. Fluctuations in each woody biomass resources were mostly less than 20% over the planning horizon. The presented research could be useful to regional forest resource managers and stakeholders involved in biomass-powered energy generation or the purchasing of woody biomass.